Isolated Soy Protein Supplementation Combined With Resistance Training Improves Muscle Strength, Mass, and Physical Performance of Aging Female Mice - Lee, Mon-Chien; Hsu, Yi-Ju; Wu, Fang-Yu; Huang, Chi-Chang; Li, Hsueh-Yu; Chen, Wen-Chyuan (Frontiers in Physiology, 2022)
Background/Purpose: In recent years, the aging population has gradually increased, and the aging process is accompanied by health-associated problems, such as loss of muscle mass and weakness. Therefore, it is important to explore alternative strategies for improving the health status and physical fitness of the aged population. In this study, we investigated the effect of soy protein supplementation combined with resistance training on changes in the muscle mass, muscle strength, and functional activity performance of aging mice. Methods: Female Institute of Cancer Research (ICR) mice were divided into four groups (n = 8 per group): sedentary control (SC), isolated soy protein (ISP) supplementation, resistance training (RT), and a combination of ISP and RT (ISP + RT). The mice in designated groups received oral ISP supplementation (0.123 g/kg/day), RT (5 days/week for a period of 4 weeks), or a combination of both ISP plus RT for 4 weeks. Afterward, we assessed muscle strength, endurance, and anaerobic endurance performance and analyzed blood biochemical and pathological tissue sections to investigate whether there were adverse effects or not in mice. Results: ISP supplementation effectively improved the muscle mass, muscle endurance, and endurance performance of aging female mice. The RT group not only showed similar results with ISP but also increased muscle strength and glycogen content. Nevertheless, the combination of ISP supplementation and RT had greater beneficial effects on muscle strength, physical performance, and glycogen levels (p < 0.05). In addition, the combination of ISP supplementation and RT had significantly increased type II muscle percentage and cross-sectional area (p < 0.05). Conclusion: Although ISP or RT alone improved muscle mass and performance, the combination of ISP with RT showed greater beneficial effects in aging mice. Our findings suggest that regular exercise along with protein supplementation could be an effective strategy to improve overall health and physical fitness among the elderly.